Segmented Regression Based on the Principle of Cut-off Polynomials with a Solved Economic Example - Kaňka, Miloš (Wydawnictwo Uniwersytetu Ekonomicznego we Wrocławiu, 2017)
This article deals with segmented regression that is based on the so called cut-off polynomials of the first, or second, respectively third order. Most of the attention is given to the inference of the system of the normal equations gained by minimisation of the criterion of the least squares method. Certain attention is also given to the calculation of the unknowns of such a system with one of the Gauss methods. Parametric equations of the output regressive curve in the given model and the determination indexes of the observed variables are inferred. Those indexes also enable to assess the "quality" of each model. The author of this article also wrote a program for the three types of segmented regression. This program helps solve the aforementioned phases in much faster and simpler way
20-th AMSE. Applications of Mathematics and Statistics in Economics. International Scientific Conference: Szklarska Poręba, 30 August- 3 September 2017. Conference Proceedings Full Text Papers, s. 235-246
Keywords: Cut-off polynomials; system of normal equations; indexes of determination ofobserved values